Effects of Typified Propolis on Mutans Streptococci and Lactobacilli: a Randomized Clinical Trial - Anauate-Netto, Camillo; Marcucci, Maria Cristina; Paulino, Niraldo; Anido-Anido, Andréa; Amore, Ricardo; Mendonça, Sergio de; Borelli Neto, Laurindo; Bretz, Walter Antonio (Brazilian Dental Science, 2013)
Objective: The aim of this study was to determine in arandomized, double-blind, placebo-controlled clinicaltrial the effects of typified propolis and chlorhexidinerinses on salivary levels of mutans streptococci (MS)and lactobacilli (LACT). Methods: One hundredpatients were screened for salivary levels of MS>100,000 CFUs/mL of saliva. All patients presentedwith at least one cavitated decayed surface. Sixtypatients met entry criteria. Subjects were adults 18-55 years old. After restoration of cavitated lesionspatients were randomized to 3 experimental groups:1) PROP-alcohol-free 2% typified propolis rinse (n =20); 2) CHX- 0.12% chlorhexidine rinse; 3) PL-placebomouthrinse. Patients rinsed unsupervised 15 mL ofrespective rinses twice a day for 1 min for 28 days.Patients were assessed for the salivary levels of MS(Dentocult SM) and LACT (Dentocult LB) at baseline,7-day, 14-day, and at 28-day visits (experimentaleffects) and at 45-day visit (residual effects). Generallinear models were employed to analyze the data.Results: PROP was superior to CHX at 14-day and28-day visits in suppressing the salivary levels of MS(p